Increasing Participation of Independent oil Palm Smallholders in Farmer Group Institution - Ananda Rexi Prayogo; Nurliza; Adi Suyatno (Institut Pertanian Bogor, 2025)
Farmer groups play an important role in the palm oil industry in terms of access to capital, production facilities, marketing, market information, and learning vehicles. However, the participation of independent smallholders in institutions, especially farmer groups, is still very limited because of the limited knowledge and awareness of farmers about the important role of these institutions. The aim of this research is to formulate an increase in the participation of independent oil palm smallholders in farmer groups in the Sambas Regency, West Kalimantan. The research used a combination of qualitative and quantitative methods with a SWOT-AHP analysis of 33 experts and ordinary informants from the government, farmer group officials, companies, wholesalers, and farmers. The results show that institutional capacity building was selected as a strategic priority for increasing farmer participation. Three efforts must be made to increase institutional capacity: compiling institutional norms/rules, holding regular meetings, and compiling group administration books. Keywords: farmer group institution, participation, oil palm smallholder